1992
DOI: 10.1073/pnas.89.10.4250
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-responsive regulatory protein controls the expression of both the pap and fan pili operons in Escherichia coli.

Abstract: The methylation blocking factor gene (mbf) in Escherichia coli is required for specific methylation inhibition of two DNA GATC sites upstream of the papBA pilin promoter and transcriptional activation of pap. Complementation and mutational analysis using paplac and ilvIH-ac operon fusions indicates that the mbf gene is identical to a recently described global regulatory gene lrp (leucineresponsive regulatory protein) that acts as a positive regulator of some genes and a negative regulator ofothers in E. coli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 36 publications
4
83
0
Order By: Relevance
“…1) (9). mbf, which maps at 19.6 min (9), is now known to be allelic to lrp (10). Transduction of insert 30 into the mbf::mTnJO-tet insertion mutant DL845 showed the close proximity of insert 30 to lrp; all 252 kanamycin-resistant transductants tested became tetracycline sensitive, implying loss of the resident mini transposon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (9). mbf, which maps at 19.6 min (9), is now known to be allelic to lrp (10). Transduction of insert 30 into the mbf::mTnJO-tet insertion mutant DL845 showed the close proximity of insert 30 to lrp; all 252 kanamycin-resistant transductants tested became tetracycline sensitive, implying loss of the resident mini transposon.…”
Section: Resultsmentioning
confidence: 99%
“…Using the approach outlined above, we have isolated insertions in lip, a gene that plays an important role in metabolism (for a review, see reference 41) and that affects both Pap and K99 fimbriation (9,10). Upon further analysis, we found that the frequency of switching of thefim invertible region, and consequently of phase variation, is sharply reduced in 1rp mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is an absolute requirement of IHF for phase variation of type I fimbriae, such that him mutants are unable to switch phase (Dorman and Higgins, 1987;Eisenstein et al, 1987). The ETEC K99 and K88 fimbriae are also regulated by LRP, which represses the expression of K88 fimbriae and activates the expression of K99 fimbriae (Braaten et al, 1992;Huisman et al, 1994). Table 1 shows that, unlike these other systems, 987P fimbriae are unaffected by mutations in lrp, dam or either of the two subunits encoding IHF (himA and himD ).…”
Section: Discussionmentioning
confidence: 99%
“…Both fimB transcription and fimE transcription are affected only slightly by mutation of lrp (3). Therefore, it is likely that the marked stimulation of fim by lrp is either direct or occurs through factors other than FimB and FimE. Lrp, a site-specific DNA-binding protein, controls a regulon of at least 40 genes in Escherichia coli, including fimbrial expression and amino acid transport, degradation, and biosyn-thesis (3,6,9,10,18,19,(22)(23)(24). The most extensive studies of Lrp have examined its role in the regulation of ilvIH transcription (19,22,23).…”
mentioning
confidence: 99%
“…Lrp binds to the promoter region of ilvIH with a high degree of cooperativity, bending the DNA to form a nucleoprotein complex (22,23). Lrp, also known as Mbf (methylation-blocking factor), participates directly in phase variation ofpapBA transcription (6,18). Pap phase variation is associated with alternate dam methylation-protection patterns and requires Lrp (18).…”
mentioning
confidence: 99%